Cavy production in South America: Current situation and future trends - Barrantes, Christian; Chauca Francia, Lilia Janine; Falconi, Patricia; Reyna, Angel (Biosciences eastern and central Africa-International Livestock Research Institute (BecA-ILRI) Hub, 2023)
Cavy production in South America takes place mainly in the Andean regions of Peru, Ecuador, Bolivia and Colombia. Since its domestication (sometime between 3000 and 6000 years ago) the cavy has been used in these countries as a source of animal protein produced with simple handling systems and adapted to the different geographical and cultural contexts. The production of cavies in these countries has grown significantly in the last years due to the promotion of its culinary and nutritional qualities. Also migration of population from rural to urban areas has brought their customs and generated a process of transculturation into the cities, which has turned massive the consumption of cavy meat. The increase in consumption has been accompanied by a growth of supply that, with some differences between countries, has allowed the development of commercial production. This adds new challenges to the ones existing in family production, which is more closely related to food and nutrition security. As a cultural food, cavies are also exported in small quantities from Peru and Ecuador (about 23.5 tons per year from both) to the USA and some European countries to cater for the demand of the Andean diaspora. The prospects of this productive activity are very good, expecting greater demand for the product in the future. However, there is need to work in promoting the association of small farmers, the creation and/or strengthening of support services to this activity (e.g. credit, technical assistance and others) and the development of technologies for both small- and largescale producers.